Jews, Christian society, and royal power in medieval Barcelona - Klein, Elka (History, languages, and cultures of the Spanish and Portuguese worlds, 2006)
1. Introduction: contexts and controversies -- 2. The community in theory and practice -- 3. The foundations of an elite -- 4. Jewish Leaders and the king, 1160-1205 -- 5. Conflict in the community, 1205-30 -- 6. The overthrow of the Nesi'im, 1230-41 -- 7. Forging a new relationship: the Jews and the king -- 8. A New elite: Jews, Christians, and the urban economy.